IMPLEMENTASI SUPERVISI AKADEMIK PADA PENERAPAN KURIKULUM MERDEKA DALAM MENINGKATKAN PROFESIONALITAS GURU - Ilham; Maruwu, Marinu; Enawaty, Eny; Halida (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study was to determine how the implementation of academic supervision based on the independent curriculum to improve teacher professionalism at SDN 8 Kartiasa. In this study, the researcher used a qualitative research approach using a descriptive method. In addition, in using data, the researcher used observation, interview, and documentation techniques. The study shows that the principal plays an important role in teacher performance, because in the case of independent curriculum changes, the principal acts as a supervisor who needs to monitor the work of teachers. This should not be interpreted as a goal, but as a beginning; This is the beginning of a learning process to improve the quality of learning. To improve the quality of education in educational institutions, we need teachers who have practical teaching skills, because teachers basically play an important role in curriculum planning and development. Thus, world-class teachers will produce quality education, which will have an impact on the birth of a quality generation that is able to compete in the era of globalization.